Zinc Accumulation Patterns and Ecological Risk Assessment in Vineyard Topsoils Under Contrasting Topographies - Van Han, Ta; Thuy An, Trinh; Hanh San, Nguyen; Thi Thanh Huong, Tran; Tien Manh, Tran; Thi Tuyet Thu, Tran; Thi Ha Nhung, Pham (VNU Journal of Science: Earth and Environmental Sciences, 2025)
In the vineyards, the terrain morphology and the intensive use of chemical fertilizers and organic mateials can pose a potential risk of soil contamination by heavy metals, particularly by Zn. Therefore, we evaluate the accumulation characteristics and bioavailability of Zn in the topsoil (0-20 cm) of a sloping vineyard in Phu Tho province (vineyard A), and in a flat terrain vineyard in Hanoi city (vineyard B). The ecological risk of Zn is assessed using the contamination factor and ecological risk index, based on total and bioavailable Zn concentrations in the soil. Results indicate that terrain, soil erosion, and farming practices exert significant impacts on the distribution of Zn in the soil. In vineyard A, a significantly higher mean total Zn content is found at the backslope of the hill (84.90 mg/kg) compared to the top of the hill (47.70 mg/kg). Meanwhile, in vineyard B, the mean total Zn content of 128.89 mg/kg is observed without any marked difference between the soil samples. On the other hand, the accumulation patterns and bioavailability of Zn in the topsoil are influenced by soil characteristics such as organic matter contents and soil particle sizes (silt and clay contents). Based on the bioavailable percentages (19.47% and 30.81% in the soil of vineyard A and B, respectively), Zn shows an overall moderate mobility. Although Zn levels are lower than the pollution limit value stipulated in Vietnamese standards (QCVN 03:2023/BTNMT) and an low adverse ecological risk is observed for both vineyards, the calculated contamination factor indicates low to considerable contamination of the soil. These findings indicate that farming practices significantly influence Zn accumulation through the use of foliar fertilizers and compost. Overall, this study on Zn accumulation characteristics and associated ecological risks in vineyards with contrasting topographies provides valuable insights into Zn dynamics in soils and supports the development of environmentally sustainable vineyard management practices.